MEMPELAJARI PERBANYAKAN PAKU ATA (LYGODIUM CIRCINNATUM (BURN. F.) SWARTZ) MELALUI KULTUR SPORA (STUDY ON DOMESTICATION OF LYGODIUM CIRCINNATUM (BURN. F.) SWARTZ TO EXCEED SPORE CULTURE) - YUSWANTI, HESTIN; DWIYANI, RINDANG; PUTRI DARMAWATI, IDA AYU (AGRITROP; Vol. 29, No. 2 Juni 2010, 2012)
This research was conducted at Tissue Culture Laboratory of Agricultural Faculty, Udayana University, from May to October 2009. The aim of this Study to acquired the best in vitro medium that was to added plant growth regulator. The results showed that plant growth regulator kinetin significantly affected to germination and protallus formation of ata fern. The M1 nedium treatment the fastest of germination formation was 19,33 day after showing (das) while the protallus formation the fastest to M3 medium was 36,17 das. In description the fastest sporofit formed to founded in M3 too (122 das).
Keywords: Lygodium, spore culture and plant growth regulator